2016
DOI: 10.1093/hmg/ddw322
|View full text |Cite
|
Sign up to set email alerts
|

Modulating ryanodine receptors with dantrolene attenuates neuronopathic phenotype in Gaucher disease mice

Abstract: Neuronopathic Gaucher disease (nGD) manifests as severe neurological symptoms in patients with no effective treatment available. Ryanodine receptors (Ryrs) are a family of calcium release channels on intracellular stores. The goal of this study is to determine if Ryrs are potential targets for nGD treatment. A nGD cell model (CBE-N2a) was created by inhibiting acid β-glucosidase (GCase) in N2a cells with conduritol B epoxide (CBE). Enhanced cytosolic calcium in CBE-N2a cells was blocked by either ryanodine or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 82 publications
(146 reference statements)
1
35
0
Order By: Relevance
“…These findings were supported by experiments performed in differentiated C2C12 cells and in primary dissociated hippocampal neurons, two cell types that express endogenous RyRs. (27) Hence, these results indicate that RyR-mediated Ca 2+ -release events suppresses autophagic flux at steps distal to the initiation of phagophore formation, and involving alteration in lysosomal function…”
Section: -Gated Intracellularmentioning
confidence: 70%
See 1 more Smart Citation
“…These findings were supported by experiments performed in differentiated C2C12 cells and in primary dissociated hippocampal neurons, two cell types that express endogenous RyRs. (27) Hence, these results indicate that RyR-mediated Ca 2+ -release events suppresses autophagic flux at steps distal to the initiation of phagophore formation, and involving alteration in lysosomal function…”
Section: -Gated Intracellularmentioning
confidence: 70%
“…(26) Second, it was reported that in a mouse model of neuropathic Gaucher disease RyR inhibition, using dantrolene, delayed the neurological pathology and increased survival. (27) The authors reported that dantrolene could partially reverse the observed alterations in autophagic flux, suggesting a possible role for RyRs in regulating autophagy. However, it was not further studied how RyRs influenced autophagy.…”
Section: -Gated Intracellularmentioning
confidence: 98%
“…73 Further, the RYR antagonist dantrolene reduces LC3-II levels in the brain of neuronopathic Gaucher disease mice exhibiting abnormal autophagy. 74 In accordance with this, a very recent study showed that basal RYR3 activity suppresses autophagic flux at the level of lysosomes. Specifically, pharmacological inhibition of endogenous (in C2C12 myoblasts and primary hippocampal neurons) or ectopically expressed (in HEK293 cells) RYRs augments autophagic flux by increasing lysosomal turnover.…”
Section: Ryr (Ryanodine Receptor)mentioning
confidence: 57%
“…Pre-clinical trials evaluating receptor antagonism (RA), AMPA-RA (Kovacs and Pearce, 2008) and NMDA-RA (Finn et al, 2013) have improved the neurobehavioral phenotypes associated with LSDs. Furthermore, a number of pharmacological agents have been explored eliciting various effects from modulating membrane fluidity (Schultz et al, 2018), modulating Ca 2+ (Chang et al, 2007) or cholesterol levels (Erickson et al, 2000;Pelled et al, 2003;Kim et al, 2007;Repa et al, 2007;Abi-Mosleh et al, 2009;Liu et al, 2010;Taylor et al, 2012;Hovakimyan et al, 2013;Nusca et al, 2014;Tanaka et al, 2014;Soga et al, 2015;Demais et al, 2016;Liou et al, 2016), and enhancing enzyme activity (Arroyo et al, 2014) via the use of neurosteroids (NS) (Griffin et al, 2004;Liao et al, 2009). There is also interest in facilitating sphingolipid degradation via the upregulation of heat shock proteins (HSP) (Chung et al, 2016;Kirkegaard et al, 2016).…”
Section: Other Therapies Under Developmentmentioning
confidence: 99%
“…(pmuts) (Xu et al, 2003) + + Gba (lnl/lnl)(Enquist et al, 2007) + + Chaperone(Dasgupta et al, 2015), CM(Liou et al, 2016), ERT (Cabrera-Salazar et al, 2010), SRT (Cabrera-Salazar et al, 2012)GLB1GM1-GangliosidosisGlb1 (−/−)(Matsuda et al, 1997) + + Chaperone(Takamura et al, 2011) …”
mentioning
confidence: 99%